Vitiligo surrounding lichenified atopic dermatitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Vitiligo and atopic dermatitis have different etiology, albeit rarely may be associated. Lesions with reduced melanic pigmentation have been described and variously interpreted in atopic dermatitis. Apart from frequent post-inflammatory hypopigmentation, particularly observed during the summer and autumn, leucoderma secondary to the use of topical corticosteroids, vitiligo-like achromia with edge hyperpigmentation, vitiligo with characteristic inflammatory raised edges, and a classical vitiligo were described. Here we report a patient with severe lichenified atopic dermatitis associated with vitiligo. Beside its classic location on the hands, a characteristic vitiligo rim was observed around the lichenified plaques.